Pengembangan Ibu Kota Negara Kepulauan dari Perspektif Etika Lingkungan - Ahmad, Amirzah; Suhendar, Bagus; Jumariyah, Siti; Delfianti, Delfianti; Ramadhan, Ramadhan (PT. Pubsains Nur Cendekia, 2025)
The occurrence of an environmental crisis certainly cannot be separated from how humans relate to the environment. This relationship has continued to develop since the existence of humans on Earth. The reality of an ecological crisis/environmental crisis becomes a context for reflection on human behavior. This research aims to evaluate the relocation of the country's capital from Jakarta to Kalimantan from an environmental ethics perspective. This research method is a literature study that involves understanding and studying theories from various literature. Law Number 3 of 2022 concerning the National Capital which discusses the principles of IKN development will use 100% environmentally friendly construction and will also implement resource efficiency and low carbon practices. However, this development also continues to raise various concerns among the community, observers, and related parties from the perspective of environmental damage, social issues, population relocation, infrastructure problems, security and national resilience issues, economic impacts, and resource competition with other regions.